PENGEMBANGAN AKTIVITAS PROYEK KOLABORASI BAGI MAHASISWA PERGURUAN TINGGI: DEVELOPMENT OF COLLABORATION PROJECT ACTIVITIES FOR HIGHER EDUCATION STUDENTS - Pemu, Nasrullah (KAMBIK: Journal of Mathematics Education, 2023)
This research aims to develop collaborative activities through project-based learning at the university level. The subjects of the study were 30 students in the mathematics education program. The development was carried out using a sequential design research method, starting from the preparation phase, teaching experiment, and retrospective analysis. To support this research, instruments such as monitoring and evaluation, documentation, activity observation sheets, and performance progress sheets were used. The data analysis was conducted using the trustworthiness method. The results showed that the activities with various targets began with activities, interviews, FGDs, and ended with constructive experiments. With these activities, positive changes were shown by students through the outcomes produced. The positive changes refer to the ability to identify problems, organize group members in constructive discussions, and perform constructive experiments to prepare solutions to the problems being solved. Moreover, this learning process further complements the students' competencies.